2024
DOI: 10.3390/su16072870
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Factors Shaping Farmer Behavior in Wastewater Utilization for Agricultural Practices: A Rapid Review

Laura Mirra,
Simone Russo,
Massimiliano Borrello

Abstract: In recent years, circular economy strategies have gained attention in agriculture, particularly regarding the utilization of wastewater as an alternative water source. This study employs a rapid review methodology to examine farmers’ attitudes toward wastewater use in agriculture. By analyzing studies in literature published from 2000 to 2023, this review identifies the key factors influencing farmers’ adoption of wastewater irrigation. These findings are valuable for policymakers seeking to develop targeted p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Agricultural reuse of unconventional water is high on Israel's list of national priorities, and the extreme water scarcity has led to the establishment of a committee to review existing regulations and propose new ones to address issues arising from unconventional water reuse. Israel's gradually updated policies and regulations are undoubtedly a good example for other Middle Eastern countries with similar climates [121,122]. The policies of developed European countries on water resources management are mostly economic and environmental.…”
Section: Discussionmentioning
confidence: 99%
“…Agricultural reuse of unconventional water is high on Israel's list of national priorities, and the extreme water scarcity has led to the establishment of a committee to review existing regulations and propose new ones to address issues arising from unconventional water reuse. Israel's gradually updated policies and regulations are undoubtedly a good example for other Middle Eastern countries with similar climates [121,122]. The policies of developed European countries on water resources management are mostly economic and environmental.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this goal, various techniques are used, such as water reuse, collection, and conservation [67]. According to Mirra et al [5] (p. 1), "public awareness campaigns and education programs can instill water-saving habits". Nevertheless, Jagtap et al [16] (p. 1) found that "there is a lack of knowledge among food manufacturers about adopting the IoT-based water monitoring system and its ability to support water minimization activities".…”
Section: Water Waste Reduction-related Knowledgementioning
confidence: 99%
“…However, water waste causes serious water shortages, which can exacerbate economic (such as food insecurity) and environmental (such as climate change) problems. The scarcity of water is a major issue that must be addressed in the XXI century [1][2][3][4], as it has led to a severe water crisis in many countries [5,6]. This has threatened food and water security and has caused migration and conflict [7].…”
Section: Introductionmentioning
confidence: 99%